2013
DOI: 10.5127/jep.029512
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Regulation in Borderline Personality Disorder: Examining the Consequences of Spontaneous and Instructed Use of Emotion Suppression and Emotion Acceptance when Viewing Negative Films

Abstract: Central to models of Borderline Personality Disorder (BPD) is the notion that dysfunctional application of avoidant emotion regulation strategies results in elevated emotional reactivity. To test this account, participants (N = 87) with varying severity of BPD underwent two negative mood inductions, the first with no particular instructions and the second following suppress or accept instructions. BPD severity was associated with greater negative affect at baseline. While BPD severity was associated with great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 55 publications
1
16
1
Order By: Relevance
“…The present findings replicate other recent studies that have compared suppression to acceptance in BPD (e.g., Evans et al, 2013, Svalik et al, 2012: Suppression and thought control resulted in a reduction of self-reported subjective distress among a relatively severe group of BPD patients. The present study added additional variables and analyses, however, and the total picture suggests caution in concluding that these recent results "challenge a core assumption of DBT and other acceptance based therapies, which eschew emotional avoidance and suppression in favour of more mindful approaches" (Evans et al, 2013, p. 561).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The present findings replicate other recent studies that have compared suppression to acceptance in BPD (e.g., Evans et al, 2013, Svalik et al, 2012: Suppression and thought control resulted in a reduction of self-reported subjective distress among a relatively severe group of BPD patients. The present study added additional variables and analyses, however, and the total picture suggests caution in concluding that these recent results "challenge a core assumption of DBT and other acceptance based therapies, which eschew emotional avoidance and suppression in favour of more mindful approaches" (Evans et al, 2013, p. 561).…”
Section: Discussionsupporting
confidence: 92%
“…Laboratory studies of EA (Levin et al, 2012) and thought suppression (Najmi & Wegner, 2008) usually reveal negative outcomes in normal controls and in some clinical populations (Abramowitz, Tolin, & Street, 2001;Rassin, 2005) but BPD patients and those higher in BPD symptoms, report reduced distress when asked to suppress and control difficult private experiences, as opposed to observing or accepting them (e.g., Chapman et al, 2009, Evans et al, 2013Svaldi et al, 2012). This interesting and discordant finding requires an account.…”
Section: Suppression and Reduced Distress Among Bpd Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…emotional avoidance or suppression in healthy samples may result in lower physiological arousal (Dunn, Billotti, Murphy, & Dalgleish, 2009), and in BPD samples, may attenuate emotional reactivity (Evans et al, 2013). To our knowledge, only one published study has examined the consequences of instructed emotional avoidance in naturalistic (versus laboratory) settings among persons with BPD features (Chapman, Rosenthal, & Leung 2009).…”
mentioning
confidence: 99%